THE IMPLEMENTATION OF TQM PRINCIPLES IN THE ACTIVITIES OF THE CERTIFICATION BODY OF PERSONNEL - Khimicheva, H. I.; Mukharovskyi, M. Ya.; Hlukhova, O. I. (Science and Transport Progress, 2006)
Realization of the TQM principles in activity of organ on certification of personnel is considered in the article.